2008
DOI: 10.1186/1471-2407-8-52
|View full text |Cite
|
Sign up to set email alerts
|

Mutation analysis of the MDM4gene in German breast cancer patients

Abstract: Background: MDM4 is a negative regulator of p53 and cooperates with MDM2 in the cellular response to DNA damage. It is unknown, however, whether MDM4 gene alterations play some role in the inherited component of breast cancer susceptibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…CK1 and CK2 are two protein kinases that participate in a wide variety of cellular processes, including DNA repair and cell cycle control. Genotyping of this polymorphims in breast cancer patients did not reveal a preferential association with this neoplasia 18. Further studies are necessary to confirm the association of this allele with cancer, in view of the paucity of data in the literature.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…CK1 and CK2 are two protein kinases that participate in a wide variety of cellular processes, including DNA repair and cell cycle control. Genotyping of this polymorphims in breast cancer patients did not reveal a preferential association with this neoplasia 18. Further studies are necessary to confirm the association of this allele with cancer, in view of the paucity of data in the literature.…”
Section: Discussionmentioning
confidence: 76%
“…The frequency of MDM4 rs4252668C was significantly higher in controls than in patients. Analyses of larger samples might be revealing for understanding its relevance in cancer in view that rs4252668 is located within p53 binding domain of MDM4 , probably affecting p53 regulation; partial data indicated that this allele was not associated with an increased risk of breast cancer 18.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As for Mdmx, there is no evidence for its involvement in heritable BrCa, 28 and in somatic BrCa reports of amplifications of the Mdmx gene vary 14 , 15 (apparently dependent on the designated threshold). Our results are consistent with low-frequency involvement of Mdm2 in luminal BrCa, but revealed high Mdmx protein levels in all the luminal BrCa cases ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%